Public Real Estate Performance Measurement: A case studyof a Bangkok Government Complex - Riratanaphong, Chaiwat; Voordt, Theo J.M. van der (Journal of Architectural/Planning Research and Studies (JARS), 2015)
Various studies have shown that corporate real estate can contribute to organisational performance. However, the concept of Public Real Estate Management (PREM) has not been well known in Thailand. This paper aims to present the concept of PREM, to describe Key Performance Indicators (KPIs) that are being used in practice, to discuss KPIs that should be developed furthermore, and to explore which organisational characteristics affect the selection and prioritisation of KPIs. The empirical study is based on data from a case study of Dhanarak Asset Development Company Limited (DAD). Research methods include interviews, walk-through observations and document analysis. The findings from the case study confirm the assumed relationships between performance measurement and organisational characteristics such as organisational objectives, structure and management style. Although the DAD organisation applies a systematic performance measurement approach, it is recommended to elaborate some KPIs furthermore such as employee satisfaction with the work environment and the rate of customer retention. The findings from the case study can be used to improve the current knowledge of the impact of public real estate management on organisational perfor-mance, and to develop a holistic performance measurement system for public real estate in Thailand.